Students' Perceptions of Project-Based Learning EFL in Grade 7 Junior High School - Ina Yuliawati (Yayasan Baru Haji Samsudin, 2025)
This study aims to analyze the project based learning learning model according to student perceptions, student views and the constraints faced by students in the project based learning learning process. Project based learning is a learning model that makes students the subject or center of learning, which focuses on learning processes that have results in the form of products. The method used in this study is descriptive qualitative, with questionnaires and interviews as instruments. one out of three students interviewed was a student who had high enthusiasm for project based learning, while the other two students had learning difficulties. In this study the researchers found that most students were very enthusiastic in the learning process, but there were still some students who experienced difficulties or obstacles in the learning process. In conclusion, the learning-based learning model according to students' perceptions is fun and easy to understand because it is directly practical. The limitation in this research is that there are few participants who are willing to be interviewed. Therefore, future studies are expected to have more participants.